Cross-ambiguity function domain multipath channel parameter estimation - Guldogan, Mehmet Burak; Arikan, Orhan (Digital signal processing, 2012)
A new array signal processing technique is proposed to estimate the direction-of-arrivals (DOAs), time delays, Doppler shifts and amplitudes of a known waveform impinging on an array of antennas from several distinct paths. The proposed technique detects the presence of multipath components by integrating cross-ambiguity functions (CAF) of array outputs, hence, it is called as the cross-ambiguity function direction finding (CAF-DF). The performance of the CAF-DF technique is compared with the space-alternating generalized expectation–maximization (SAGE) and the multiple signal classification (MUSIC) techniques as well as the Cramér–Rao lower bound. The CAF-DF technique is found to be superior in terms of root-mean-squared-error (rMSE) to the SAGE and MUSIC techniques.